Evaluation of the Stability of the Subjects with Anterior Cruciate Injuries Reconstruction - Aghdam, Hossein Akbari; Kavyani, Mahsa; Bosak, Maryam; Karimi, Mohammad Taghi; Motififard, Mehdi (The Journal of Knee Surgery, 2020)
Anterior cruciate ligament (ACL) is the most frequently injured ligament in the knee and is often injured during sport-related activities. ACL injuries influence the abilities of the subjects during standing and walking. Although early surgical intervention is preferred treatment for the majority of knee surgeons, the effect of this approach on postural stability of patients is not fully understood. Therefore, the aim of this study was to determine the difference between stability of ACL-reconstructed subjects before and after surgery. A group of 15 consecutive ACL injured patients participated in this study. Postural stability of the patients was evaluated 1 week before and 6 months after surgery (ACL reconstruction with hamstring autograft). A Kistler force plate was used to evaluate center of pressure (COP) sway during quiet standing. The mean values of the COP parameters were obtained in pre and postsurgery conditions. Paired sample t-test was used to evaluate the difference between the stability parameters of the two conditions. The significant point was set at 0.05. The mean value of path length of COP velocity in mediolateral (ML) direction was 1,485.57 ± 479.42 mm and 2,641.33 ± 996.26 mm before and after surgery, respectively (p-value = 0.01). Although the mean value of COP velocity in anteroposterior and ML directions increased after surgery, the difference was only significant for velocity in ML direction (p-value = 0.049). The results of this study showed that the standing stability of those with ACL reconstruction decreased significantly after ACL reconstruction, which may be due to the effects of the surgery on sensory mechanism of ACL and inability of patients to return to their previous deep sense perception and knee proprioception.
Keywords: knee; anterior cruciate ligament reconstruction; stability; quiet standing